The Effect of Helminth Infections and Their Treatment on Metabolic Outcomes: Results of a Cluster-Randomized Trial. (30th August 2019) - Sanya, Richard E; Webb, Emily L; Zziwa, Christopher; Kizindo, Robert; Sewankambo, Moses; Tumusiime, Josephine; Nakazibwe, Esther; Oduru, Gloria; Niwagaba, Emmanuel; Nakawungu, Prossy Kabuubi; Kabagenyi, Joyce; Nassuuna, Jacent; et al.
Abstract: Background: Helminths may protect against cardiometabolic risk through effects on inflammation and metabolism; their treatment may be detrimental to metabolic outcomes. Methods: In a cluster-randomized trial in 26 Ugandan fishing communities we investigated effects of community-wide intensive (quarterly single-dose praziquantel, triple-dose albendazole) vs standard (annual single-dose praziquantel, biannual single-dose albendazole) anthelminthic treatment on metabolic outcomes, and observational associations between helminths and metabolic outcomes. The primary outcome, homeostatic model assessment of insulin resistance (HOMA-IR), and secondary outcomes (including blood pressure, fasting blood glucose, lipids) were assessed after 4 years' intervention among individuals aged ≥10 years. Results: We analyzed 1898 participants. Intensive treatment had no effect on HOMA-IR (adjusted geometric mean ratio, 0.96 [95% confidence interval CI, .86–1.07]; P = .42) but resulted in higher mean low-density lipoprotein cholesterol (LDL-c) (2.86 vs 2.60 mmol/L; adjusted mean difference, 0.26 [95% CI, −.03 to .56]; P = .08). Lower LDL-c levels were associated with Schistosoma mansoni (2.37 vs 2.80 mmol/L; −0.25 [95% CI, −.49 to −.02]; P = .04) or Strongyloides (2.34 vs 2.69 mmol/L; −0.32 [95% CI, −.53 to −.12]; P = .003) infection. Schistosoma mansoni was associated with lower total cholesterol (4.24 vs 4.64 mmol/L; −0.25 [95% CI, −.44 to −.07]; P = .01) and moderate to heavy S. mansoni infection with lower triglycerides, LDL-c, and diastolic blood pressure. Conclusions: Helminth infections improve lipid profiles and may lower blood pressure. Studies to confirm causality and investigate mechanisms may contribute to understanding the epidemiological transition and suggest new approaches to prevent cardiometabolic disease. Clinical Trials Registration: ISRCTN47196031. Abstract : In a cluster-randomized trial, intensive (vs standard) anthelminthic treatment increased low-density lipoprotein cholesterol. In observational analyses, schistosome and Strongyloides stercoralis infections were associated with reduced serum lipids, and heavy schistosome infection with lower blood pressure. Helminth elimination may promote cardiovascular disease risk.